Brexit and Cyber Security. Issue 3 (16th April 2019) - Stevens, Tim; O'Brien, Kevin
Abstract : Brexit is likely to have an effect on UK–EU cyber security cooperation. While there are ongoing reasons to be positive about the state of UK–EU cyber security, Tim Stevens and Kevin O'Brien show how Brexit will have negative impacts on cybercrime policing and cyber threat intelligence sharing, particularly in a 'no-deal' scenario, and argue that the absence of a negotiated settlement will damage the cyber security of the UK and the EU.